Criminal Law Issues of Norms Encouraging the Surrender of Weapons in Illicit Trafficking - Hambardzumyan, Virab; Arakelyan, Sergey (Bulletin of Yerevan University C: Jurisprudence, 2025)
Legal norms encouraging the surrender of weapons in illicit trafficking play an important role both in crime prevention and in promoting lawful behavior among citizens. In this context, it is especially important to analyze the changes introduced in recent years to the criminal legislation of the Republic of Armenia. Part 4 of Article 335 of the new Criminal Code of the Republic of Armenia, adopted on May 5, 2021, contains an incentive provision regarding the voluntary surrender of illegally circulating weapons, which substantially differs in content from the corresponding provision enshrined in Part 5 of Article 235 of the Criminal Code adopted on April 18, 2003. The purpose of this article is to examine the substantive changes that have occurred in these legal provisions and to assess their impact on criminal policy and law enforcement practice. In order to achieve the stated objective, the article conducts a comparative analysis of the incentive norms provided in both the former and current Criminal Codes, as well as the peculiarities of their application, while also identifying key issues and challenges that may arise in the course of law enforcement practice. The study was carried out using both general (interdisciplinary) and specialized methods of scientific inquiry, such as dogmatic, comparative legal, and logical analysis, as well as the method of legal modeling. As a result of the research conducted in the article, a number of conclusions were drawn, based on which well-founded proposals aimed at improving the incentive norm were presented.